(untitled) (Vietnam Journal of Community Medicine, 2026)
The objective of this study: is to survey the learning motivation of third-year medical students at Hai Phong University of Medicine and Pharmacy and describe some related factors. Research method: a cross-sectional descriptive study on 522 third-year medical students at Hai Phong University of Medicine and Pharmacy. Students completed a survey using a 7-point Likert scale. Results: 63% of students had good learning motivation, with extrinsic motivation being higher than intrinsic motivation (p<0.001). Factors related to academic motivation include gender (OR=2.22; 95%CI=1.54-3.20; p<0.001), self-confidence (OR=1.73; 95%CI=1.04-2.89; p=0.03), club participation (OR=1.71; 95%CI=1.19-2.45; p=0.003), receive help from teachers when needed (OR=1.80; 95%CI= 1.07-2.88; p=0.025) and academic achievement scholarships (OR=1.92; 95%CI=1.2-3.1; p=0.007). Conclusion: The percentage of students with good academic motivation is quite high; however, there is a need to enhance intrinsic motivation. Considerations could include increasing counseling and support for female students, encouraging student participation in clubs, and increasing scholarships and academic advisors to boost student motivation.